Envisioning the Future of Culturally Responsive Counseling: A Bibliometric Perspective - Fadilah, Ela Nur; Nursalim, Mochamad; Purwoko, Budi; Winingsih, Evi; Habsy, Bakhrudin All; Oktaviana, Dian (Universitas Negeri Padang, 2025)
Cultural diversity in a global educational environment demands a counseling approach that is able to respond to the social dynamics and cultural identities of students. Multicultural counseling is an important strategy in supporting an equal, inclusive, and social justice-based learning process. This study aims to map the development of culturally responsive counseling theory and practice through bibliometric analysis. A total of 316 scientific articles indexed in the Scopus database in the period 2020–2024 were analyzed using VOSviewer and Bibliometrix R software. The results of the study indicate that multicultural counseling has shifted from a cultural awareness approach to interventions based on evaluation, social justice, and integration of local wisdom. The findings also reveal the dominance of contributions from Western countries, as well as the weak representation of the Asian and Global South regions, which indicates an inequality in knowledge production. This study provides a concrete contribution in formulating the direction of developing a cross-cultural competency-based counselor education curriculum and data-based policy advocacy, emphasizing the need for more equal global collaboration. These findings can be the basis for designing counselor training models and psychosocial service policies that are more contextual and sensitive to cultural diversity.